Diagnosis, Diagnosis Differensial dan Penatalaksanaan Immunosupresif dan Terapi Sumsum Tulang pada Pasien Anemia Aplastik - Thaha ..; AA Wiradewi Lestari; I Wayan Putu Sutirta Yasa (E-Jurnal Medika Udayana, 2014)
Anemia aplastic is anemia with bone marrow failure characterized by pancytopenia and at themost case with hypoplasia bone marrow. The incidence of anemia aplastic is 3 -6 case per 1million persons per year. Clinical presentations of anemia aplastic are anemia syndrome,leukopenia will cause infection, and thrombocytopenia will cause bleeding. Diagnosis of anemiaaplastic is based on bicytopenia and pancytopenia without malignancy, infiltration, andsuppression to bone marrow. Treatments for anemia plastic are main therapy, supportive therapyand long-term therapy. Main therapy is avoiding the caustic agent. Supportive therapy giveswhen there is a symptom from anemia, neutropenia and thrombocytopenia. Long-term therapy isimmunosuppressive therapy and bone marrow therapy.